2018
DOI: 10.1016/j.paid.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Finding middle ground between intellectual arrogance and intellectual servility: Development and assessment of the limitations-owning intellectual humility scale

Abstract: Recent scholarship in intellectual humility (IH) has attempted to provide deeper understanding of the virtue as personality trait and its impact on an individual's thoughts, beliefs, and actions. A limitations-owning perspective of IH focuses on a proper recognition of the impact of intellectual limitations and a motivation to overcome them, placing it as the mean between intellectual arrogance and intellectual servility. We developed the Limitations-Owning Intellectual Humility Scale to assess this conception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 25 publications
4
77
0
2
Order By: Relevance
“…The use of two measures of IH in this research makes it more difficult to compare results between the studies conducted (Studies 1 and 2 versus Studies 3-5), however, the use of multiple measures also adds to the richness of the findings. Although Haggard et al (2018) have found multiple measures of IH to intercorrelated strongly, the current research points out that there may be differences in how distinct assessments of IH relate to measures of knowledge.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 54%
See 2 more Smart Citations
“…The use of two measures of IH in this research makes it more difficult to compare results between the studies conducted (Studies 1 and 2 versus Studies 3-5), however, the use of multiple measures also adds to the richness of the findings. Although Haggard et al (2018) have found multiple measures of IH to intercorrelated strongly, the current research points out that there may be differences in how distinct assessments of IH relate to measures of knowledge.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 54%
“…Need for cognition, cognitive reflection, intellectual engagement, and curiosity Previous research has indicated that the general population uniquely attributes the desire for knowledge to intellectually humble individuals, including love of learning, curiosity, and inquisitiveness (Samuelson et al, 2015). Some conceptualizations of IH include a desire for knowledge and love of learning (Haggard et al, 2018). In the current studies, effortful thinking and love of learning were not an inherent part of the definition of IH, but were considered relevant outcomes.…”
Section: Thinking Styles Interpersonal Dispositions and Learning Gomentioning
confidence: 73%
See 1 more Smart Citation
“…This scale is proven applicable across cultures, as has been demonstrated by its use in Germany (Alfano et al, 2017). (Davis et al, 2016;Haggard et al, 2018;Hoyle et al, 2016;Krumrei-Mancuso, Haggard, LaBouff, & Rowatt, 2020;McElroy et al, 2014;Meagher et al, 2015;Porter & Schumann, 2018). Furthermore, they are more tolerant of the ambiguous, and less closed-minded and dogmatic (Haggard et al, 2018;Hoyle et al, 2016).…”
Section: Self-and Informant-report Measurementioning
confidence: 89%
“…Regarding the relationship between IH and other conceptions, there is a spectrum between intellectual arrogance or dogmatism and intellectual servility or timidity. IH is a delicate balance in this spectrum (Haggard et al, 2018;Hazlett, 2012;Wang & Yang, 2019). Furthermore, it has been suggested that IH is conceptually different from other psychological attributes, such as dogmatism, belief superiority, openness, attitude correctness, and uncertainty about what one believes, just to name a few (Leary et al, 2017).…”
Section: Definition and Characteristicsmentioning
confidence: 99%